Ideal planting space for merbau (Intsia bijuga) forest plantations in Papua based on distance-dependent competition (Biodiversitas Journal of Biological Diversity, 2018)
Sirami EV, Marsono D, Sadono R, Imron MA. 2018. Ideal planting space for merbau (Intsia bijuga) forest plantations in Papua based on distance-dependent competition. Biodiversitas 19: 2219-2231. Distance-based competition between merbau (Intsia bijuga (Colebr.) Kuntze) and neighboring trees could be applied to determine the planting space between merbau trees and shade trees in plantations. This research was conducted to identify the characteristics of merbau competition with neighboring trees and determine the ideal spacing of merbau trees. The sampling design using was the systematic line technique with hypothetical plot and sample tree as the quadrant center. The competitors were determined using a virtual high approach and header contact. Distance-based competitions were identified using the Hegyi index. Sixteen species had the highest competition index because of their dominance in the tree structure, namely Pometia coriacea, Intsia bijuga, Pimelodendron amboinicum, Horsfieldia laevigata, Palaquium amboinense, Pometia pinnata, Garcinia sp., Spathiostemon javensis, Prunus costata, Sterculia macrophylla, Terminalia complanata, Lepiniopsis ternatensis, Horsfieldia irya, Dysoxylum octandrum, Buchanania arborescens, and Ficus similis. Merbau responded to the high intensity of competition by tilting its canopy in the opposite direction to the position of the competitors’ canopy, making an irregular canopy shape, and growing the first branch at the lowest point on the stem. The ideal planting space for merbau trees in the plantations was 3-7 m.
Keywords: Distance-dependent competition; Gunung Meja; merbau plantations; planting space; West Papua